2014
DOI: 10.1080/0972060x.2014.961038
|View full text |Cite
|
Sign up to set email alerts
|

Sub-lethal Activity of Plant Volatile Essential Oils in Management of Red Flour BeetleTribolium castaneum(Coleoptera: Tenebrionidae)

Abstract: Stored food faces severe damage due to infestation by insects. The essential oils extracted from leaves of Mentha arvensis and peels of Citrus reticulata by hydrodistillation method were screened as fumigant for chronic activity against red flour beetle Tribolium castaneum (Coleoptera: Tenebrionidae) in laboratory assay. Both essential oils showed chronic activity in a dose dependent manner. Fumigation with sublethal concentration of essential oils significantly (p < 0.01) reduced hatchability of adults, inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Regarding the species investigated in the present study, the literature offers reports on the effect of the EO from Citrus limon against pests of interest to veterinary medicine (Aboelhadid, Mahrous, Hashem, Abdel‐Kafy, & Miller, ), human medicine (Selvakumar, Gokulakrishnan, Elanchezhiyan, & Deepa, ), agriculture (Martins, Zago, Costa, Araujo Junior, & Carvalho, ) and grain storage (Karabörklü, Ayvaz, Yilmaz, & Akbulut, ). The EO from Citrus reticulata is also reported to have action against pests of interest to human medicine (Badawy et al, ), agricultural activities and grain storage (Badawy et al, ; Mishra, Tripathi, & Tripathi, ), including the two‐spotted spider mite (Choi, Lee, Park, & Ahn, ). Moreover, the EO from Citrus aurantiifolia has demonstrated action against the two‐spotted spider mite in a previous study (Pavela, Stepanycheva, Shchenikova, Chermenskaya, & Petrova, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the species investigated in the present study, the literature offers reports on the effect of the EO from Citrus limon against pests of interest to veterinary medicine (Aboelhadid, Mahrous, Hashem, Abdel‐Kafy, & Miller, ), human medicine (Selvakumar, Gokulakrishnan, Elanchezhiyan, & Deepa, ), agriculture (Martins, Zago, Costa, Araujo Junior, & Carvalho, ) and grain storage (Karabörklü, Ayvaz, Yilmaz, & Akbulut, ). The EO from Citrus reticulata is also reported to have action against pests of interest to human medicine (Badawy et al, ), agricultural activities and grain storage (Badawy et al, ; Mishra, Tripathi, & Tripathi, ), including the two‐spotted spider mite (Choi, Lee, Park, & Ahn, ). Moreover, the EO from Citrus aurantiifolia has demonstrated action against the two‐spotted spider mite in a previous study (Pavela, Stepanycheva, Shchenikova, Chermenskaya, & Petrova, ).…”
Section: Discussionmentioning
confidence: 99%
“…Citrus reticulata is also reported to have action against pests of interest to human medicine (Badawy et al, 2017), agricultural activities and grain storage (Badawy et al, 2017;Mishra, Tripathi, & Tripathi, 2014), including the two-spotted spider mite (Choi, Lee, Park, & Ahn, 2004). Moreover, the EO from Citrus aurantiifolia has demonstrated action against the two-spotted spider mite in a previous study (Pavela, Stepanycheva, Shchenikova, Chermenskaya, & Petrova, 2016).…”
Section: Fumigant and Residual Contact Bioassaymentioning
confidence: 90%
“…They found that oil caused 50–60% of egg mortality, and 18 and 28% of larval and pupal mortality, respectively, at same dose and 24 h of exposure. In T. castaneum, M. arvensis oil was found to reduce 67.50 and 61.25% acetylcholinesterase activity over control ( Mishra et al, 2014 ) after 24 h of fumigation. Saroukolai et al (2014) reported that M. spicata essential oil showed 259.73 and 75.31 ppm LC 50 value against fourth star larvae of potato beetle Leptinotarsa decemlineata (Say) by fumigant bioassay and oil also exhibited 39.26% feeding deterrent index against the adults at 16 ppm.…”
Section: Biological Activity Of Essential Oils Of Mentha mentioning
confidence: 92%
“…The inhibition of acetylcholinesterase causes a desensitisation of the acetylcholine receptor and leads to obstruction of the influx transmission (Fournier et al 1992). Mishra et al (2014) studied the acetylcholinesterase activity of T. castaneum against Citrus reticulata Linnaeus (Rutaceae) and Mentha arvensis Linnaeus (Lamiaceae) essential oils at LC 50 doses. Acetylcholinesterase activity was reduced as a result of both essential oil treatments: 0.049 μM of substrate hydrolysed min −1 mg −1 of protein with C. reticulata and 0.054 μM of substrate hydrolysed min −1 mg −1 of protein with M. arvensis, compared to 0.080 μM of substrate hydrolysed min −1 mg −1 of protein in the control.…”
Section: Discussionmentioning
confidence: 99%